Electrothermal Reliability of the High Electron Mobility Transistor (HEMT) - Abdelhamid Amar (MDPI AG, 2021)
The main objective of our paper is to propose an approach to studying the mechatronic system’s reliability through the reliability of their high electron mobility transistors (HEMT). The operating temperature is one of the parameters that influences the characteristics of the transistor, especially the electron mobility that represents an advantage over other transistor’s families. Several factors can influence this temperature. Thanks to thermal modeling, it is possible to determine the factors representing a great impact on the operating temperature, such as the power dissipation at the active area of the transistor and the reference temperature above the substrate. In our reliability study, these analytical methods, such as First and Second Order Reliability Methods (FORM and SORM, respectively), were used to analyze the HEMT reliability. Thanks to the coupling between two models—the reliability model coded on Matlab and the thermal modeling with Comsol multiphysics software—the reliability index and the failure probability of the studied system were evaluated.